Analysis of Farmers’ Characteristics and Satisfaction with the Use of PT XYZ’s Organic Fertilizer in Losari Subdistrict, Brebes Regency - Akhmad Mediranto; Popong Nurhayati; Handaya (Pelopor Publikasi Akademika, 2026)
The adoption of organic fertilizer among Indonesian farmers remains relatively limited despite its potential to support sustainable agriculture and improve long-term soil productivity. This study aimed to identify the characteristics of farmers using PT XYZ’s organic fertilizer and assess their satisfaction with the product and supporting services in Losari Subdistrict, Brebes Regency. The study employed a quantitative descriptive approach involving 38 rice farmers selected through purposive sampling from a population of 50 users. Primary data were collected through structured questionnaire interviews and analyzed using descriptive analysis, Importance Performance Analysis (IPA), and the Customer Satisfaction Index (CSI). The results showed that organic fertilizer users represented only 0.69% of the 5,504 rice farmers in Losari Subdistrict, indicating substantial potential for market expansion. Respondents were predominantly male farmers aged 40–60 years, with extensive farming experience and small- to medium-sized farms. The IPA results identified product guarantees, reusable and varied packaging sizes, conformity of results with product claims, and product accessibility as priority areas for improvement. The CSI score reached 67.88%, placing farmers in the satisfied category, although most attributes showed negative performance–expectation gaps. The study concludes that farmer satisfaction is generally positive but not optimal, requiring improvements in distribution, packaging, quality assurance, demonstration plots, and technical assistance.